2019
DOI: 10.1111/ene.14061
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐early continuous cardiac monitoring improves atrial fibrillation detection and prognosis of patients with cryptogenic stroke

Abstract: Biotronik, Inc gently provided 35 of the implantable cardiac monitors (Biomonitor®) required for this study. No other conflicts of interest regarding the present work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Our results are in accordance with a recent meta‐analysis of RCTs and observational studies suggesting that prolonged cardiac monitoring is associated with more than 2‐fold higher chance of incident PAF detection and anticoagulation initiation, and a 65% relative risk reduction in stroke recurrence for patients with cryptogenic stroke or TIA 17 . Our observations parallel the results of another single‐center observational study from Spain reporting 70% reduction in risk of recurrent stroke in the ICM compared to the noninvasive cohort 18 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in accordance with a recent meta‐analysis of RCTs and observational studies suggesting that prolonged cardiac monitoring is associated with more than 2‐fold higher chance of incident PAF detection and anticoagulation initiation, and a 65% relative risk reduction in stroke recurrence for patients with cryptogenic stroke or TIA 17 . Our observations parallel the results of another single‐center observational study from Spain reporting 70% reduction in risk of recurrent stroke in the ICM compared to the noninvasive cohort 18 …”
Section: Discussionsupporting
confidence: 91%
“…17 Our observations parallel the results of another single-center observational study from Spain reporting 70% reduction in risk of recurrent stroke in the ICM compared to the noninvasive cohort. 18 We also reported a median elapsed time of 4 months between ICM insertion and PAF. This finding further highlights the importance of implantable cardiac monitoring to uncover PAF in cryptogenic stroke, because the duration of prolonged Holter monitoring scarcely exceeds 1 month.…”
Section: Discussionmentioning
confidence: 89%
“…In the SURPRISE study [35], the implantation of the insertable cardiac monitor was also long after the CrS (median of 69 days) and the study population was younger than ours. Moreover, a recent study has shown that the diagnosis of AF by using an insertable cardiac monitor compared to conventional strategy increased AF detection after CrS [36].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies in a greater population should confirm our findings; in particular, the values of myocardial deformation, as a consequence of their variability. AF guidelines [38] define clinical AF as lasting at least 30 s; although the AF burden related outcomes are not clear, we consider the definition of ≥1 min's duration, given that this cut-off value showed prognostic implications in a previous study after CrS [36].…”
Section: Discussionmentioning
confidence: 99%
“…The relative simplicity of this predictive method makes it suitable for population screening of at-risk groups or those who cannot co-operate easily with clinical tests. The method may also be applied to analyze previously-collected data, e.g., to investigate links between subclinical AF and cryptogenic stroke (Healey et al, 2012) or development of dementia, when early screening would be especially useful (Cuadrado-Godia et al, 2020).…”
Section: Controlsmentioning
confidence: 99%